Oxidative Stress in SLE T Cells, Is NRF2 Really the Target to Treat? - Ohl, Kim; Tenbrock, Klaus (Frontiers in Immunology, 2021)
Oxidative stress is a major component of cellular damage in T cells from patients with systemic lupus erythematosus (SLE) resulting amongst others in the generation of pathogenic Th17 cells. The NRF2/Keap pathway is the most important antioxidant system protecting cells from damage due to oxidative stress. Activation of NRF2 therefore seems to represent a putative therapeutic target in SLE, which is nevertheless challenged by several findings suggesting tissue and cell specific differences in the effect of NRF2 expression. This review focusses on the current understanding of oxidative stress in SLE T cells and its pathophysiologic and therapeutic implications.